2021
DOI: 10.1007/s00027-021-00843-2
|View full text |Cite
|
Sign up to set email alerts
|

Clonality in invasive alien macrophytes in Kashmir Himalaya: a stage-based approach

Abstract: BackgroundThe invasion of non-native species is a major cause of the global biodiversity loss and creates enormous economic costs. What determines alien invasive species dominance over native plant species is still little known, but there is an emerging pattern that many of the world's worst invasive plants are successful invaders due to the signi cant connection between their clonal traits and invasiveness. Freshwater ecosystems are relatively more prone to decline and extinction of species caused by biologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Mounger et al (2021) reported that 70% of global invasive plants are clonal plants. Wani et al (2022) also believed that positive correlation between clonality and invasiveness. Alternanthera philoxeroides (Mart.)…”
Section: Introductionmentioning
confidence: 99%
“…Mounger et al (2021) reported that 70% of global invasive plants are clonal plants. Wani et al (2022) also believed that positive correlation between clonality and invasiveness. Alternanthera philoxeroides (Mart.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, almost all of the taproots and rhizomes are processed into medicinal slices after harvesting (Zheng et al, 2020).Although the chemical compositions of the taproots and rhizomes are similar, consumers prefer the larger diameter of the taproots slices, which has a red, smooth and intact epidermis (Huang et al, 2019) and the larger the diameter of the slices, the higher the price (Long, 2017). Since there is a trade-off in resource allocation between the taproots and rhizomes, over-developed rhizomes will inevitably lead to a reduction in the yield and quality of the taproots (Wani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%